2012
DOI: 10.1126/science.1215507
|View full text |Cite
|
Sign up to set email alerts
|

238 U/ 235 U Systematics in Terrestrial Uranium-Bearing Minerals

Abstract: One sentence summary:238 U/ 235 U ratios for U-bearing accessory minerals from a diverse suite of terrestrial rocks indicate a >5‰ range with an average zircon value of 238 U/ 235 U = 137.818 ± 0.045 (2σ) which is consistent with the composition of other terrestrial and meteoritic reservoirs. 2, 3). However, a robust λ 235 U can only be determined with U-Pb analyses using a tracer calibration that is traceable to SI units and free of other potential sources of bias, so we refrain from suggesting this value be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
260
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 621 publications
(300 citation statements)
references
References 75 publications
7
260
0
2
Order By: Relevance
“…They found a significantly lower average ratio of 137.837. Hiess et al [324] confirmed the basic finding and published results for a large number of terrestrial minerals. They suggest that the U variations of the order of 1 ‰ have been observed in naturally occurring terrestrial materials [317].…”
Section: Uraniumsupporting
confidence: 80%
“…They found a significantly lower average ratio of 137.837. Hiess et al [324] confirmed the basic finding and published results for a large number of terrestrial minerals. They suggest that the U variations of the order of 1 ‰ have been observed in naturally occurring terrestrial materials [317].…”
Section: Uraniumsupporting
confidence: 80%
“…Analytical parameters and metadata are listed in supplementary information 1. (Hiess et al, 2012). The Pb/Pb and U/Pb ratios were normalised to bracketing primary reference material 91500, based on the average measured value of the reference material compared to the ratio determined by ID-TIMS (Wiedenbeck et al, 1995).…”
Section: Geochronological Methodsmentioning
confidence: 99%
“…DR3). This tuff yielded abundant euhedral zircons that we treated with the chemical abrasion method prior to acquiring U-Pb isotope dilution thermal ionization mass spectrometry data ( Figs U ratio of zircon (Hiess et al, 2012). For comparisons with previously published dates, our new date can be recalculated using the legacy Table DR3).…”
Section: New Age Constraint For the Mamainse Point Successionmentioning
confidence: 99%